Evaluation of the thermal properties of water and water/ethanol carbon-based nanofluids - Castro-Rodríguez, Berenice; Carranza-Chávez, Francisco J.; Beltrán, Alberto; Zavala-Guillén, Ivett; Sauceda-Carvajal, Daniel; Rodríguez-Hernández, Ana G.; Soto-Herrera, Gerardo; Borbón-Núñez, Hugo A. (Fullerenes, nanotubes, and carbon nanostructures, 2025)
Nanofluids have the potential to improve the performance of heat transfer systems by enhancing the fluid thermal properties. In the work presented here the stability, density, thermal conductivity, and viscosity of two types of nanofluids containing amorphous carbon nanospheres dispersed in water and in a water/ethanol mixture were evaluated experimentally at volumetric concentrations from 0.2% to 2.0% in the temperature range 10-40 °C. The carbon nanospheres were synthesized through hydrothermal oxidation of glucose. Obtained zeta potential values between −51.5 and −151.0 mV revealed the higher stability of the water/ethanol nanofluids, however, the water-based nanofluids exhibited greater thermal conductivity, reaching a maximum increment of 9.29% at 40 °C and 2% of concentration. The maximum thermal conductivity increment of the water/ethanol nanofluids was 5.32%. In addition, substantial viscosity increments were obtained for both types of nanofluids. The maximum viscosity increments found at 40 °C and 2% of concentration were 66.92% for the water-based nanofluids, and 74.70% for the water/ethanol nanofluids. The changes of density were considerably low, remaining under 2% for both nanofluid types at all cases. In addition, a specific heat value of 770.7 J/kg·K was obtained for the solid nanospheres and used to explore the nanofluids specific heat behavior through a suitable correlation.